Macronutrients distribution and cycling of pineapple planted on tropical peat - Ahmed, Osumanu Haruna; Mohd Hanif, Ahmad Husni; Musa, Mohamed Hanafi; Syed Rastan, Syed Omar (Universiti Putra Malaysia Press, 2000)
This research quantifies P, K, Ca and Mg inputs, losses, retention in soil, and uptake and returns for burnt and unburnt pineapple residue in management practices. Treatments used were: leaves residue removed and no fertilization (LRRNF), leaves residue burnt and no fertilization (LRBNF), leaves residue removed and fertilization (LRRF), and leaves residue burnt and fertilization (the usual practice) (LRBF). Nitrogen, P and K were applied in the forms of urea (46.00% N), China phosphate rock (CPR 14.00% P) and muriate of potash (MOP 49.80% K) at the rates of 701.04, 35.56, and 556.56 kg N, K, and P per ha respectively. Rainfall simulator was used for surface runoff measurement on burnt plots before planting. Soil sampling at the depths of 0-5, 525 and . 25 cm were done before planting, during and after fertilization stages. Extractable P, K, Ca and Mg were extracted using the double-acid method. The subtraction method was used to estimate P, K, Ca and Mg leached (kg per haY. At maturity, plants were sampled from each treatment and partitioned into roots, stem, leaves, fruit, crown and peduncle, and the dry weights, of P, K, Ca and Mg contents determined. Molybdate blue method and atomic absorption spectrophotometer were used in determining P, K, Ca and Mg in soil, plant parts and rainwater, K, Ca and Mg additions from fertilizer, ash and precipitation for LRBF were estimated at 54.25, 816.68, 103.31 and 23.54 kg per ha, and those of LRRF (fertilizer and precipitation) were 35.56, 576.05, 100.17, and 4.93 kg P, K, Ca, and Mg per ha, respectively. The estimated amounts of P, K, Ca and Mg lost under LRBF were 18.44, 300.45, 66.06 and 8.63 kg per ha and in the case of LRRF, the losses were 23.19, 244.88, 45.79 and 5.49 kg per ha. Leaching was the major source of P, K, Ca and Mg loss for both practices and this was attributed to inappropriate fertilization frequency. A positive balance of P, K, Ca and Mg was recorded for LRBF, 46.00% P, 28.00% K, 20.00% Ca and 27.00% Mg which could be recycled after cropping. In the case of LRRF, a positive balance ofP, K and Ca was observed. About 60.00%P, 20.00% K, 13.00% Ca and 36.47% Mg get recycled for LRRF.